The Effect of Pre-Operative Education on Anxiety in Patients Undergoing Percutaneous Coronary Intervention - Pramono, Cahyo; Jumaiyah, Wati; Natashia, Dhea; Sofiani, Yani (Indonesian Journal of Global Health Research, 2024)
Myocardial infarction (MI) describes the process of myocardial cell death caused by ischemia or an imbalance between myocardial oxygen supply through the coronary arteries and demand. Coronary heart disease remains the leading cause of death worldwide, and in Indonesia it still shows that coronary heart disease is the highest cause of death at all ages after stroke. Providing preoperative education by providing relevant health care information and preparing physically and psychologically can reduce patient anxiety. The purpose of this research is to determine the effect of preoperative education on the anxiety of patients undergoing PCI. The method uses a quasi-experimental design. The research method used a quasi-experiment with an intervention group and a control group. The sampling technique used Purposive sampling. The number of samples in this study was 46 respondents, 23 intervention groups and 23 control groups. The study was conducted in May - June 2024 in the ICCU room of PKU Muhamadiyah Gamping Hospital, with a data collection time allocation of 15 minutes to measure anxiety and provide pre-operative education. Pre-test anxiety measurements were carried out during the ACS medical diagnosis and scheduled for PCI, then pre-operative education was given with booklet media, post-test measurements were carried out one hour before the PCI was carried out. The instrument used was the STAI (State-Trait Anxiety Inventory) questionnaire with 20 question. Data analysis using the Independent Samples Test. The result is a P value of 0.00, which means there is a difference in anxiety between the intervention group and the control group. The average anxiety of the intervention group pre-test was 34.39 decreasing to 30.57, and the control group pre-test anxiety average was 34.17 decreasing to 33.22. The conclusion is that pre-operative education is effective in reducing anxiety in patients undergoing PCI.